(untitled) (Práxis Educativa, 2017)
The aim of this paper is to analyze the pedagogical theories of Physical Education and, from its presuppositions, understand their conceptions of man, concepts of difference and inclusion relating to these conceptions. This is a theoretical study that uses reference works of the area and classical works that substantiate these conceptions. We understand that difference and inclusion, implicit in those concepts, are conceived from biology, culture, communication and work, and that teaching practice is oriented for distinct purposes and perspectives. We conclude that it is necessary to move beyond the explanations of difference and inclusion in order to recover the work as a central category, of which the explanation is based on social inequality and the need for new and transformative educational practices beyond the ones disseminated in contemporary social and educational policies. Keywords: Difference. Inclusion. Pedagogic conceptions of Physical Education.